Meninjau Ulang Teks Perang dalam Kitab Suci Ibrani : Sumbangan dari Keluaran 14:13-14, 15:3 - Tony Wiyaret Fangidae (Societas Dei: Jurnal Agama dan Masyarakat, 2021)
This article carefully discusses the war texts in the Hebrew Bible used to legitimize war in solid form. This concern is discussed specifically regarding the texts that narrate war in the Hebrew Bible (Ex 14: 13-14, 15: 3), which are used for war purposes and in the name of God. The use of scriptural texts and God’s involvement in war shifts the war paradigm from common war to holy war. This article focuses on the discourse of war in the Hebrew Bible and tries to draw several conclusions that can help the reader understand the polemic of the relationship between the Hebrew Bible and war. This article closes with a statement that the war texts in the Hebrew Bible has the capacity to deconstruct the paradigm of war as well as to encourage readers to put forward liberation and freedom.